Positron Emission Tomography scanning in Anti-Neutrophil Cytoplasmic Antibodies-Associated Vasculitis. Issue 20 (May 2015) - Kemna, Michael J.; Vandergheynst, Frédéric; Vöö, Stefan; Blocklet, Didier; Nguyen, Thomas; Timmermans, Sjoerd A.M.E.G.; van Paassen, Pieter; Cogan, Elie; van Kroonenburgh, Marinus J.P.G.; Tervaert, Jan Willem Cohen; Masoomi., Michael
<x xml:space="preserve">Abstract</x> Abstract Tools for evaluation of disease activity in patients with anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) include scoring clinical manifestations, determination of biochemical parameters of inflammation, and obtaining tissue biopsies. These tools, however, are sometimes inconclusive. 2-deoxy-2-[18F]-fluoro-D-glucose (FDG) positron emission tomography (PET) scans are commonly used to detect inflammatory or malignant lesions. Our objective is to explore the ability of PET scanning to assess the extent of disease activity in patients with AAV. Consecutive PET scans made between December 2006 and March 2014 in Maastricht (MUMC) and between July 2008 and June 2013 in Brussels (EUH) to assess disease activity in patients with AAV were retrospectively included. Scans were re-examined and quantitatively scored using maximum standard uptake values (SUVmax). PET findings were compared with C-reactive protein (CRP) and ANCA positivity at the time of scanning. Forty-four scans were performed in 33 patients during a period of suspected active disease. All but 2 scans showed PET-positive sites, most commonly the nasopharynx (n = 22) and the lung (n = 22). Forty-one clinically occult lesions were found, including the thyroid gland (n = 4 patients), aorta (n = 8), and bone marrow (n = 7). The amount of hotspots, but not the highest observed SUVmax value, was higher if CRP levels were elevated. Seventeen follow-up scans were made in 13 patients and showed decreased SUVmax values. FDG PET scans in AAV patients with active disease show positive findings in multiple sites of the body even when biochemical parameters are inconclusive, including sites clinically unsuspected and difficult to assess otherwise.